Development of a Liveworksheet-Based E-LKPD Oriented Toward Independent Character to Improve Students’ Mathematics Learning Outcomes - Welly Lucardo; Siti Aisyah; Dewi Fitriana (FKIP - Universitas Riau, 2026)
This study was motivated by the low mathematics learning outcomes of elementary school students in Lubuk Basung District, where most students scored below the minimum mastery criterion. In addition, students showed a lack of independent learning habits, relying heavily on teacher guidance. To address these issues, this research aimed to develop an electronic student worksheet (E-LKPD) using Liveworksheet, designed to foster student independence and improve mathematics achievement. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Participants included fourth-grade students from several elementary schools in Lubuk Basung District. Data were collected through observations, interviews, expert validations, student response questionnaires, and achievement tests, and were analyzed both qualitatively and quantitatively. The results indicated that the developed E-LKPD was highly valid (95–96%), practical with positive student responses (87–89%), and effective in improving outcomes. The experimental class achieved an average score of 83.04, higher than the control class average of 75.87, with the t-test confirming a significant difference. In conclusion, the Liveworksheet-based E-LKPD not only enhanced students’ mathematics achievement but also cultivated independent learning, making it a valuable tool for classroom practice.